Determinação de resíduos de compostos orgânicos em água por microextração líquido-líquido dispersiva (DLLME) E GC-(TQ)MS/MS - Martins, Manoel Leonardo (2010)
The use of chemicals, which generates a lot off benefits, is responsible for the contamination of soil, water and foods. The concern about contamination of surface and ground water systems by pesticides has grown in scientific circles, especially by the presence of pesticides and other compounds in water sources. Thus, rapid analytical methods, sensitive and efficient must be developed in order to verify the concentration levels of pesticides and other organic compounds in water samples agree with those established by law to protect human health and the environment media. This study aimed to optimize, validate and implement an extraction method to determine residues of mononitro, ketones, trifluralin, oxirane, lindane, 2,4-D ester, chlorpyrifos, bromoketal, α-endosulfan, β-endosulfan and endosulfan sulfate in samples of tap water, industrial wastewater and groundwater by Dispersive Liquid-Liquid Microextraction (DLLME) modified and Gas Chromatography with Mass Spectrometry Tandem using Triple Quadrupole type (GC-(TQ)MS/MS). The method is based on the rapid injection, with a syringe, of a mixture of an extractor solvent (50 μL of carbon tetrachloride) and an dispersor solvent (2.0 mL acetone) previously cooled (ice batch, 0 - 4 °C) in an aqueous sample (5.0 mL), contained in a 10 mL graduated glass tube with conical bottom, with no pH correction and cooled (ice batch, 0 - 4 °C). It is not necessary to stir the sample in this step. Remove 25 μL of the sedimented phase separated by simple sedimentation for 10 min. from the bottom of conical tube with a microsyringe and transferred to a vial of 200 μL for GC- (TQ)MS/MS determination. The preconcentration factor obtained was 100 times. The method was validated by determining the limits of detection and quantification limits (LOD and LOQ), linearity, precision and accuracy. The calibration curves showed adequate linearity between 0.05 e 10 μg L-1 with coefficients of determination higher than 0.993. The method showed good recovery values between 70 and 115%, RSD(%) ranged from 10.9 to 17.2%, LOQs between 0.02 and 0.09 μg L-1, and was considered adequate for the analysis of pesticide residues and other organic compounds evaluated in water samples. After validation, the method was applied to samples of drinking water, industrial wastewater and groundwater. No pesticide residues and other organic compounds evaluated were found in the water samples tested.